Pokój ryski a odzyskanie polskiego dziedzictwa literackiego - Pietrzkiewicz, Dorota (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
The Peace of Riga is considered by historians as one of the most important documents of the interwar period in Eastern Europe. It established the central belt of the western border of Russia, forced Marshal Józef Piłsudski to abandon plans to establish an Eastern European federation, which had an impact on the character of the recovering Republic, and sanctioned the borders and political system of Belarus and Ukraine. These issues have been considered by researchers, as reflected in the literature on the subject, but only a few papers discuss issues related to the restitution of book collections and archival documents. The purpose of the present article is to highlight the recovery of works of Polish literary heritage carried out under the Peace of Riga. It shows the involvement of the Polish scientific community in receiving manuscripts, prints (including incunabula), engravings, and archives of Polish provenance from Russian institutions. Today, the confiscated Polish manuscripts and prints that could not be recovered under the Peace of Riga are subject to the international cooperation of librarians from Warsaw and St. Petersburg.